Kenaf (Hibiscus cannabinus L.): A promising fiber crop with potential for genetic improvement utilizing both conventional and molecular approaches - Al-Mamun, Md; Rafii, Mohd Y.; Misran, Azizah; Berahim, Zulkarami; Ahmad, Zaiton; Hasan Khan, Md Mahmudul; Oladosu, Yusuff; Arolu, Fatai (Taylor and Francis, 2023)
Kenaf is a fiber crop belonging to the genus Hibiscus (Malvaceae), and the potential of this plant, its multipurpose use, and its environmentally friendly cellulose have placed kenaf at the forefront of both commercial and sub-sistence farming. Due to inadequate agricultural practices, low production potential, and photoperiodism, the yields of fiber are relatively low. The varietal development in kenaf is hindered by a lack of knowledge of its heredity, which also affects its successful usage and protection of important germplasm. The amount and production potential of kenaf are enhanced by identifying and exploring obtainable genetic resources for the development of high-yield cultivars. Knowledge of existing natural genetic variation and its availability is important for this highly valued crop’s genetic improvement. This review summarized recent advances in kenaf varietal improvement using marker-assisted breeding, genetic linkage maps, and morphological and molecular assessment of genetic diversity. Existing issues were discussed to produce scientific references for identifying photo-insensitive kenaf genotypes.